VALUES OF JAVA CULTURE - Elvian Mutiara; Yazida Ichsan; Ismail Fauzi; Husein Ma'ruf (FORUM PAEDAGOGIK, 2022)
Â Research on the moral values of Javanese culture needs to be done because this study it will reveal and explain various kinds of Javanese culture, especially the culture which has moral values in it. For some people, culture is only a tradition left by their ancestors, then passed down from generation to generation, and needs to be preserved. Yet every Javanese culture has its own history, meaning, and value. This study uses a qualitative descriptive analysis method. The approach used is the library research approach or the library method. Javanese culture is a culture originating from Java. If we go back to history, of course, Javanese culture is not far from the influence of Hinduism, animism, and dynamism. Some Javanese cultures that still exist today are used by the community: salametan, tedak siten, wayang, manners, bancaan weton, politeness, and many more. Among all Javanese cultures, some of them have moral values. This is what needs to be applied and maintained by every parent in educating children's morals. Besides introducing Javanese culture to children. Parents have invited their children to maintain Javanese culture through Javanese cultural moral values. By implementing character education through Javanese culture, then we have preserved Javanese culture and practiced moral values in it in everyday life.Â Â